Ekwiwalenty greckiego [niewolnik, sługa prowadzący chłopca do szkoły] (1Kor 4,15, Gal 3,24.25) w?polskich renesansowych przekładach Nowego Testamentu = Equivalents for the Greek [a tutor i. e. a guide and guardian of boys] (1Cor 4,15 and Gal 3,24.25) in polish Renaissance renderings of the New Testament - Lisowski, Tomasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The Greek lexeme[a tutor i. e. a guide and guardian of boys]; a slave who were charged with the duty of supervising the life and morals of boys belonging to the better class? appeared in the Greek text of the New Testament three times (in 1Cor 4,15 and Gal 3,24.25), being used by Paul to build semantic metaphorical images. The lexeme [a tutor i. e. a guide and guardian of boys], with its meaning establishing in a distant cultural reality, did not have an explicit equivalent in the Renaissance Polish.
Keywords: przekład biblijny; techniki translacyjne; polskie renesansowe przekłady Nowego Testamentu; polszczyzna renesansowa; rendering of the Bible; translational techniques; Polish Renaissance renderings of the New Testament; Renaissance Polish